Voluntary Reading and Narrative Speaking Instructional Strategies to Enhance Students' Speaking Ability - Dianawati, Heffy (University of Muhammadiyah Prof. DR. HAMKA, 2018)
This research aimed at investigating classroom strategies to encourage students’ participation in speaking activity. Specifically, the study addressed three research questions: 1) what are the strategies to help students encounter difficulty in speaking English in classroom, 2) to what extent does voluntary reading prior speaking activity help students develop ideas and motivation to speaking English in the classroom, 3) does the application of narrative speaking strategy in speaking classroom affect students’ speaking achievement?  The participants of the research were students at Al Azhar 28 Islamic Junior Secondary School aged 13 to 14 who joined English extracurricular program. A mix method design combining two research strands, qualitative and quantitative, was adopted. The data were collected through multiple methods: speaking test, focus group interview, and observation. The study showed positive finding. Based on the qualitative data drawn, doing a voluntary reading could diminish students’ anxieties in speaking, decrease speaking block, increase students’ motivation to do good speaking task, and improve students’ social awareness. Meanwhile, the narrative speaking fostered students’ speaking fluencies, grammar accuracy, pronunciation, and knowledge measured through observations and speaking rubrics to achieve the data analysis. The result showed there was significant improvement on students’ speaking skill shown by significance or p-value <0.001 or less than α = 0.05 with standard deviation of the pretest was 3.70 and posttest was 3.96.  Keywords: voluntary reading, speaking skill, teaching and learning speaking, conference publications